Long Non-coding RNA and mRNA Profile of Liver Tissue During Four Developmental Stages in the Chicken - Ning, Chunyou; Ma, Tianyuan; Hu, Silu; Xu, Zhongxian; Zhang, Pu; Zhao, Xiaoling; Wang, Yan; Yin, Huadong; Hu, Yaodong; Fan, Xiaolan; Zeng, Bo; Yang, Mingyao; et al. (Frontiers in Genetics, 2020)
The liver is the major organ of lipid biosynthesis in the chicken. In laying hens, the liver synthesizes most of the yolk precursors and transports them to developing follicles to produce eggs. However, a systematic investigation of the long non-coding RNA (lncRNA) and mRNA transcriptome in liver across developmental stages is needed. Here, we constructed 12 RNA libraries from liver tissue during four developmental stages: juvenile (day 60), sexual maturity (day 133), peak laying (day 220), and broodiness (day 400). A total of 16,930 putative lncRNAs and 18,260 mRNAs were identified. More than half (53.70%) of the lncRNAs were intergenic lncRNAs. The temporal expression pattern showed that lncRNAs were more restricted than mRNAs. We identified numerous differentially expressed lncRNAs and mRNAs by pairwise comparison between the four developmental stages and found that VTG2, RBP, and a novel protein-coding gene were differentially expressed in all stages. Time-series analysis showed that the modules with upregulated genes were involved in lipid metabolism processes. Co-expression networks suggested functional relatedness between mRNAs and lncRNAs; the DE-lncRNAs were mainly involved in lipid biosynthesis and metabolism processes. We showed that the liver transcriptome varies across different developmental stages. Our results improve our understanding of the molecular mechanisms underlying liver development in chickens